2019
DOI: 10.2147/copd.s214961
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>CYP2B6</em> genetic polymorphisms influence chronic obstructive pulmonary disease susceptibility in the Hainan population</p>

Abstract: IntroductionChronic obstructive pulmonary disease (COPD) is a lung disease closely related to exposure to exogenous substances. CYP2B6 can activate many exogenous substances, which in turn affect lung cells. The aim of this study was to assess the association of single-nucleotide polymorphisms (SNPs) in CYP2B6 with COPD risk in a Chinese Han population.Materials and methodsGenotypes of the five candidate SNPs in CYP2B6 were identified among 318 cases and 508 healthy controls with an Agena MassARRAY method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…CYP2B6 rs4803420 G/T was associated with a decreased COPD risk compared to GG genotype, and rs1038376 A/T was related to an increased COPD risk compared with the AA genotype in the co-dominant and dominant models. 29 In the study by Korytina et al demonstrated that rs2787094 and rs2280091 GG haplotypes of ADAM33 gene significantly increased the incidence of COPD. 30 The study of Ding et al found that the genotype TT of IREB2 rs13180 significantly decreased the COPD risk, but failed to find the association between the SNPs with COPD risk in a Han population in the further stratification analysis.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2B6 rs4803420 G/T was associated with a decreased COPD risk compared to GG genotype, and rs1038376 A/T was related to an increased COPD risk compared with the AA genotype in the co-dominant and dominant models. 29 In the study by Korytina et al demonstrated that rs2787094 and rs2280091 GG haplotypes of ADAM33 gene significantly increased the incidence of COPD. 30 The study of Ding et al found that the genotype TT of IREB2 rs13180 significantly decreased the COPD risk, but failed to find the association between the SNPs with COPD risk in a Han population in the further stratification analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of high levels of NNAL in urine was related to the exacerbation of COPD symptoms such as dyspnea, poor functional status, and more restricted activity [ 28 ]. Previously, in the Hainan population of China, polymorphisms in CYP2B6 were related to susceptibility to COPD [ 29 ]. However, in our population, polymorphisms in CYP2B6 and CYP2A6 were associated with a lower risk of suffering from COPD; this indicates that in Latin America, Mexico had a minor prevalence of disease (7.8%) but had an annual cigarette consumption of 500–1499 per person [ 30 ], equal to Brazil, Uruguay, Chile, and Venezuela, which have a major prevalence at 10% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Du et al also showed the genetic variants of GSTP1 , HO-1 , and SOD-3 were correlated with COPD susceptibility [ 7 ]. Besides, other studies have been reported that PDE4D , FAM13A , CYP2B6 gene polymorphisms may exert effects on COPD susceptibility [ 8 10 ]. These findings highlighted the important role of genetic polymorphisms in the occurrence of COPD.…”
Section: Introductionmentioning
confidence: 99%